2005
DOI: 10.1128/mcb.25.17.7494-7504.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in Dbf4 Motif M Impairs Interactions with DNA Replication Factors and Confers Increased Resistance to Genotoxic Agents

Abstract: Dbf4/Cdc7 is required for DNA replication in Saccharomyces cerevisiae and appears to be a target in the S-phase checkpoint. Previously, a 186-amino-acid Dbf4 region that mediates interactions with both the origin recognition complex and Rad53 was identified. We now show this domain also mediates the association between Dbf4 and Mcm2, a key Dbf4/Cdc7 phosphorylation target. Two conserved sequences, the N and M motifs, have been identified within this Dbf4 region. Removing motif M (Dbf4⌬M) impairs the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 50 publications
3
62
1
Order By: Relevance
“…This observation is reminiscent of the fact that specific Cdc7 and Dbf4 mutations that alter sensitivity to HU and other genotoxic agents can be isolated in both budding (5,25,27) and fission yeast (28 -31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is reminiscent of the fact that specific Cdc7 and Dbf4 mutations that alter sensitivity to HU and other genotoxic agents can be isolated in both budding (5,25,27) and fission yeast (28 -31).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of DNA damage caused by UV radiation or by the alkylating drug methyl methanesulfonate, Cdc7 was shown to be important for induced mutagenesis (5,25). Finally, deletion analysis has defined an N-terminal domain within the Dbf4 protein, which is dispensable for DNA replication, but is required for maintaining cell viability in HU, possibly by targeting the kinase to stalled forks (26,27). Similarly, a growing body of genetic evidence indicates that HSK1, the fission yeast Cdc7 homologue is important for HU and alkylating agent-induced checkpoint responses (28 -31).…”
mentioning
confidence: 99%
“…The association of Rad53 and Dbf4 mediates the Rad53-dependent phosphorylation of Dbf4 and the consequent inhibition of Cdc7, thus preventing late origin firing (7)(8)(9)(10). This interaction involves the N-terminal region of Dbf4 that folds as a modified BRCA1 C-terminal (BRCT) domain (4,(11)(12)(13).…”
mentioning
confidence: 99%
“…The structure revealed that this region of Dbf4 folds as a modified BRCT domain that requires an additional N-terminal α-helix to form a stable unit (Figure 7). A fragment of Dbf4 consisting of the canonical BRCT domain but missing the additional helix did not support binding to the FHA1 domain of the checkpoint effector kinase, Rad53 [9,10,31,88]. It was proposed that this additional helix (α0) defines, at least in part, the interaction interface [10].…”
Section: Dbf4/rad53: a Case Study For Phosphorylation-independent Brcmentioning
confidence: 99%